THE EFFECT OF EDUCATION POLICIES ON PHYSICAL EDUCATION, HEALTH AND SPORTS COURSE IN NORTH CYPRUS - Mustafa Behlül; Çağda Kıvanç Çağanağa, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Physical education and sports courses enable students to become functional in developing their leadership and creative skills, as well as diligent, hardworking, self-discipline, productive, harmonious, tenacious, contestatory, cooperative, understanding, determined and respectful to each other. The aim of this study is to analyse the effect of educational policies on physical education, health and sports courses in North Cyprus. The population of this study comprised teachers and principals working in schools during the fall term of 2020–2021. In this context, the sample of this study was determined by using the ‘maximum variation sampling method’. Research data were collected via a semi-structured interview method. In the research data, the physical education, health and sports curriculum is inconsistent, not fully implemented and the law and curriculum do not comply with the Northern Cyprus education programme policy.